1999
DOI: 10.1007/s000180050359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide on the contraction of skeletal muscle

Abstract: A review of the literature suggests that the effects of nitric oxide (NO) on skeletal muscles fibers can be classified in two groups. In the first, the effects of NO are direct, due to nitrosation or metal nitrosylation of target proteins: depression of isometric force, shortening velocity of loaded or unloaded contractions, glycolysis and mitochondrial respiration. The effect on calcium release channels varies, being inhibitory at low and stimulatory at high NO concentrations. The general consequence of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 140 publications
4
96
1
Order By: Relevance
“…In contrast, L-NAME, the non-selective NOSs inhibitor, postponed the cold-induced increase in MnSOD activity seen in the untreated group in the early phase to day 21 of late cold exposure and decreased CuZnSOD activity during the acclimation to cold. It was found that L-arginine enhanced exercise-induced NOSs activation and NO production, which improves aerobic capacity (Maxwell et al, 2001), mechanical and metabolic muscle capability (Maréchal and Gailly, 1999;Ohta et al, 2007) and increases glucose oxidation (Fu et al, 2005). In contrast, L-NAME, through inhibition of NOSs and a decrease in V. Petrovic and others NO availability, diminished skeletal muscle contractions, as well as glucose uptake and oxidation (Robberts et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, L-NAME, the non-selective NOSs inhibitor, postponed the cold-induced increase in MnSOD activity seen in the untreated group in the early phase to day 21 of late cold exposure and decreased CuZnSOD activity during the acclimation to cold. It was found that L-arginine enhanced exercise-induced NOSs activation and NO production, which improves aerobic capacity (Maxwell et al, 2001), mechanical and metabolic muscle capability (Maréchal and Gailly, 1999;Ohta et al, 2007) and increases glucose oxidation (Fu et al, 2005). In contrast, L-NAME, through inhibition of NOSs and a decrease in V. Petrovic and others NO availability, diminished skeletal muscle contractions, as well as glucose uptake and oxidation (Robberts et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, NO is produced by the activity of constitutively expressed endothelial and neuronal NO synthase (NOS), localized on the surface of the sarcolemmal membrane and the endothelial plasmalemmal caveolae, as well as by inducible NOS, the localization of which varies depending on the state of the cell (Kobzik et al, 1995;Bates et al, 1996). NO regulates many physiological functions of skeletal muscle including glucose uptake and oxidation (Young et al, 1997), mitochondriogenesis (Puigserver et al, 1998), contractile functions (Joneschild et al, 1999;Maréchal and Gailly, 1999), blood flow (Brevetti et al, 2003) and fatty acid oxidation (Jobgen et al, 2006), as well as muscle repair through satellite cell activation and the release of myotrophic factors (Anderson, 2000;Brunelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The role of L-arginine in the regulation of skeletal muscle fuel metabolism at rest and exercise is well documented (Puigserver et al, 1998;Maréchal and Gailly, 1999;Brevetti et al, 2003;Jobgen et al, 2006;Lee-Young et al, 2010). We also recently reported that L-arginine supplementation improves skeletal muscle antioxidative defense (Petrović et al, 2008).…”
Section: P<0001 Pgc-1α/ppars In Skeletal Muscle In the Coldmentioning
confidence: 93%
“…In addition to exercise and thermogenesis, metabolic recruitment of skeletal muscle can be induced by some nutriceutical agents, including L-arginine. In skeletal muscle, Larginine regulates glucose uptake and oxidation, fatty acid oxidation (Jobgen et al, 2006), mitochondriogenesis (Puigserver et al, 1998), contractile function (Joneschild et al, 1999;Maréchal and Gailly, 1999) and blood flow (Brevetti et al, 2003). L-arginine is the precursor for nitric oxide (NO) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review conducted by Maréchal and Gailly 1999 (15) suggests that the nitric oxide effects over the muscle fibers may be classified in two groups: direct action and mediated by the cyclic guanidine monophosphate (cGMP). In the former group, the nitric oxide acts directly over the proteins leading to depression of the isometric strength, decreasing the velocity of the resisted or not resisted contractions, glycolysis and mitochondria breathing.…”
Section: Pre Postmentioning
confidence: 99%